Handbook of Climate Change Adaptation - Leal Filho, Walter (Springer Berlin Heidelberg : Imprint: Springer, 2015)
The Handbook of Climate Change Adaptation addresses the scientific, social, political and cultural aspects of climate change in an integrated and coherent way. The multi-volume reference focuses on one of the key aspects of climate change: adaptation and how to handle its impacts on physical, biotic and human systems, analyzing the social and normative scientific concerns and presenting the tools, approaches and methods aimed at management of climate change impacts. The high-quality, interdisciplinary contributions provides state-of-the-art descriptions of the topics at hand with the collective aim of offering, for a broad readership, an authoritative, balanced and accessible presentation of the best current understanding of the nature and challenges posed by climate change. It serves not only as a valuable information source but also as a tool to support teaching and research and as help for professionals to assist in decision-making.